Evaluation of adults' acumen exerted from cerebral stress with quantified anthropometric indices using bioelectrical impedance analysis - Kusum Tara; Md Hasibul Islam; Shadhon Chandra Mohonta; Ajay Krisna Sarkar (Sensing and Bio-Sensing Research, 2024)
This work considers cerebral stress-struck adults to assess their ‘acumen’ with four quantified anthropometric indices like cell membrane capacitance (CM), total body impedance (TBI), total body fat (TBF), and total body water (TBW). Primarily, a bio-impedance model of the epithelial tissue structure of human body has been presented and anatomized considering mental stress driven hormonal changes happen inside human body to propose several preambles. Secondly, an intelligence quotient (IQ) test designed to create ‘racing’ thoughts has been conducted right before measuring indices using bioelectrical impedance spectroscopy (BIS) method. Finally, juxtaposed investigations to vindicate the correlation between bio-impedance model-implied preambles and the variance of the four quantified indices were made by comparing them to the IQ test outcomes. This article reports, an effectively innervated nervous system having homeostasis endocrine human anatomy with CM, TBI, TBF, and TBW, in the range of 1.0–2.1 nF, 470–550 Ω, 7.9–20%, and 56.8–80%, respectively for the subjects whose acumen is classified as “Class-A'', while “Class-B'' subjects are also presented with other distinct quantified indices. The outcomes of this work are expected to be a paradigm in the digital judgment of adults' psychological engagement to any tasks.